A Mobile Technology-Based Empowerment Model for Arabic Language Teachers in Developing Animated Learning Videos at Rural Islamic Boarding School - S. Ali Jadid Al Idrus; M. Syarifuddin; Leny Cahyani; Radin Paras Raharja (Jurnal Penelitian Pendidikan IPA, 2025)
Teachers in rural Islamic boarding schools (pesantren) often have limited access to digital training and few opportunities to develop innovative instructional media for Arabic language instruction. This study investigates how mobile-based training can empower Arabic language teachers to create animated learning videos and examines the types of mentoring that facilitate this process. Using a qualitative Participatory Action Research (PAR) design, the study engaged 16 teachers from three rural pesantren in iterative cycles of training, hands-on practice, reflection, and guided mentoring. Data were collected through in-depth interviews, observations, documentation of teacher-produced videos, and continuous digital communication. The findings reveal a six-phase empowerment process: initial digital literacy gaps, emerging awareness of the pedagogical potential of mobile technology, step-by-step skill acquisition through experiential practice, negotiation of technical and contextual challenges, internalization of digital competence accompanied by increased self-efficacy, and early instructional implementation of animated videos. Mentoring, characterized by personalized guidance, responsive troubleshooting, modeling of complex procedures, and sustained online support, was essential in maintaining engagement and overcoming technological barriers. Teachers reported greater confidence, stronger professional agency, and improved capacity to design context-appropriate digital media. The study accomplishes that mobile-based training supported by intensive mentoring can effectively empower teachers in resource-limited Islamic educational settings. The proposed six-phase empowerment model offers a scalable and contextually adaptable framework for teacher development initiatives in rural and underserved environments